Burn first aid knowledge, attitude, and practice among medical interns of a tertiary care center: A descriptive cross-sectional study - Bajracharya, Amir; Mishra, Aakash (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Burn injuries are a significant public health concern with immediate and long-term consequences. This study assessed the knowledge, attitude, and practice of burn first aid among medical interns in a tertiary care center. Methods: A descriptive cross-sectional study was conducted among medical interns at a tertiary care center. A structured questionnaire was used to collect data on the burn first aid knowledge, attitude, and practical skills of medical interns. The data were analyzed using appropriate statistical methods. Results: The study involved 89 medical interns aged between 23 and 29 years, with 60.7% male participants. Of them, 51(57.3%) reported no prior exposure to burn and 17(19.1%) received formal training in burn first-aid priorly. The study found that 85 participants had good knowledge (95.5%), with only 4.5% having poor knowledge. Attitude assessment revealed 66(74.16%) participants had unfavorable attitudes, while 25.84% had a favorable attitude towards burn first aid. All participants had a good level of practice. Conclusions: The study emphasizes the need for targeted interventions to enhance burn first aid KAP among medical interns in tertiary care centers, including structured training programs, continuing medical education, positive attitudes, and hands-on practical skills training.